An examination of the complex associations between religiousness and femininity among US Christian women. Issue 7 (9th August 2017) - Power, Leah; Cook, Stephen W.
ABSTRACT: Although various forms of religiousness have been found to be associated with women's body image, sexuality, and personal and professional roles, these studies have failed to examine multiple aspects of religiousness and femininity (i.e., conformity to feminine norms) concurrently. The current study explored the association between femininity and religiousness among women using multivariate definitions of these constructs. As hypothesised, there were multiple significant associations between religiousness and femininity. In terms of the more complex, multivariate relationships, more conservative and "traditional" religiousness was found to be associated with high sexual fidelity, adherence to domestic roles, and adherence to being sweet and nice. Also, minimal engagement in religiousness was associated with low levels of modesty, low adherence to being nice, and more emphasis on being in a romantic relationship. Several simpler, bivariate relationships were also found as hypothesised.